Relational dynamic and personality of parents of children with special educational needs (SEN) - Călin, Mariana Floricica; Sandu, Mihaela Luminița; Alistar, Crina Florina (Technium Social Sciences Journal, 2022)
The subject of this thesis represents a subject of real interest in today's society, especially among specialists in psychological or psycho-educational fields. Moreover, addressing this issue represents a real need to identify and explore the family environment in which children with SER are found, as well as the dynamics in the relationship of the parents in that situation and changes in it, as well as at the level of the whole family environment, with the prognosis of a diagnosis of their children. So, this paperwork aims to become a theoretical and applied support for specialists who carry out psychological and educational activities with SER children, as well as their parents, but not only that, it also have an educational purpose. Starting from an empirical remark based on events from professional experience, both the personality of the two parties involved in the family union or in the couple, influences the way in which the two partners relate to the situation they face.